Ac susceptibility studies under dc fields in superspinglass nanomaghemite-multiwall carbon nanotube hybrid - Ramos-Guivar J.A. (2021)
Magnetic properties of maghemite (?-Fe2O3 ) nanoparticles grown on activated multiwall carbon nanotubes have been studied by alternating current (AC) magnetic susceptibility experiments performed under different temperatures, frequencies, and applied magnetic fields. Transmission elec-tron images have suggested that the ?-Fe2O3 nanoparticles are not isolated and have an average size of 9 nm, but with a relatively broad size distribution. The activation energies of these 9 nm ?-Fe2O3 nanoparticles, determined from the generalized Vogel–Fulcher relation, are reduced upon increasing the direct current (DC) field magnitude. The large activation energy values have indi-cated the formation of a superspinglass state in the ?-Fe2O3 nanoparticle ensemble, which were not observed for pure ?-Fe2O3 nanoparticles, concluding that the multiwall carbon nanotubes favored the appearance of highly concentrated magnetic regions and hence the formation of superspinglass state. Magnetic relaxation studies, using Argand diagrams recorded for DC probe fields (<20 kOe) below the magnetic blocking temperature at 100 and 10 K, have revealed the presence of more than one relaxation process. The behavior of the ensemble of ?-Fe2O3 nanoparticles can be related to the superspinglass state and is also supported by Almeida–Thouless plots. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.